TRAINING FOR THE MAKING OF LIQUID ORGANIC FERTILIZER BANANA WEEVIL AT DESA SP 7 CECAR, BTS ULU DISTRICT, MUSI RAWAS REGENCY - FITRIA LESTARI; Andriana Sofiarini; Nur Nisai Muslihah (Pelita Eksakta, 2021)
Fertilizer are organic and inorganic substances that are indispensable for plant growth and development. However, the use of inorganic fertilizers that do not follow the procedure will cause the planted plants to become infertile dut to the decline in the pyhsical, chemical, and biological quality of the soil. Therefore, one solution to minimize it is to use banana weevil that is not further processed by the community in SP 7 Cecar village. The method used in this activity is training to make liquid fertilizer for banana weevil. The results of the activity showed an increase in the skills of the SP 7 Cecar community in processing banana weevil into liquid organic fertilizer by 97,5%. Based on the activity, it can be concluded that all parts of the banana, including banana weevil can be used to produce useful and valuable products.